2018
DOI: 10.1111/ppl.12835
|View full text |Cite
|
Sign up to set email alerts
|

2,4‐D‐induced parthenocarpy in pear is mediated by enhancement of GA4 biosynthesis

Abstract: Parthenocarpy, the productions of seedless fruit without pollination or fertilization, is a potentially desirable trait in many commercially grown fruits, especially in pear, which is self-incompatible. Phytohormones play important roles in fruit set, a process crucial for parthenocarpy. In this study, 2,4-dichlorophenoxyacetic acid (2,4-D), an artificially synthesized plant growth regulator with functions similar to auxin, was found to induce parthenocarpy in pear. Histological observations revealed that 2,4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…Plant hormones play key roles in parthenocarpic fruit growth. Parthenocarpy can be induced by the exogenous application of plant hormones, such as gibberellins (GAs), auxins, and melatonin (Cong et al, 2018;Liu et al, 2018a;Liu et al, 2018b), as well as the regulation of endogenous hormone contents (Mesejo et al, 2010;Ding et al, 2013;Sugiyama et al, 2014;Niu et al, 2015). Application of GAs can be used for this purpose in many horticultural plants, such as apple (Watanabe et al, 2008), loquat (Aslmoshtaghi and Shahsavar, 2013) and pear (Liu et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Plant hormones play key roles in parthenocarpic fruit growth. Parthenocarpy can be induced by the exogenous application of plant hormones, such as gibberellins (GAs), auxins, and melatonin (Cong et al, 2018;Liu et al, 2018a;Liu et al, 2018b), as well as the regulation of endogenous hormone contents (Mesejo et al, 2010;Ding et al, 2013;Sugiyama et al, 2014;Niu et al, 2015). Application of GAs can be used for this purpose in many horticultural plants, such as apple (Watanabe et al, 2008), loquat (Aslmoshtaghi and Shahsavar, 2013) and pear (Liu et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Phytohormones play important roles in young fruit development. Young pear fruits contain high level of auxin, and low level of ethylene [49]. Further functional analyses of PcERF003 and PcIAA13 may help to elucidate the links between the effects of auxin and ethylene on anthocyanin and/or PA accumulation in young developing pear fruit.…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, CPPU-induced parthenocarpy is partly dependent on enhanced gibberellin and auxin biosynthesis and the application of PAC can significantly decrease gibberellin content 30 . Our previous studies have indicated that GA 4+7 , 2,4-dichlorophenoxyacetic acid (2,4-D), and melatonin (MT) can all induce parthenocarpy, which in pear is dependent on gibberellin 12,24,35 . To investigate whether gibberellin also plays a key role in CPPU-induced parthenocarpy in pear, we sprayed CPPU supplemented with PAC (a gibberellin synthesis inhibitor) on bagged 'Dangshansu' pear flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Auxin was the first phytohormone discovered to induce parthenocarpy in plants 7,8 . Previous studies have indicated that an ectopic supply of auxin or auxin-like substances can induce parthenocarpy in strawberry 9 , tomato 10 , pear 11,12 , and eggplant 13 . In addition, changes in auxin biosynthesis and signaling pathways have been shown to induce parthenocarpic fruit set and fruit development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation